Chronic demyelination-induced seizures. (27th March 2017) - Lapato, Andrew S.; Szu, Jenny I.; Hasselmann, Jonathan P.C.; Khalaj, Anna J.; Binder, Devin K.; Tiwari-Woodruff, Seema K.
Highlights: Seizures are observed in both early onset and progressive forms of multiple sclerosis. Chronic cuprizone administration induced demyelination in the corpus callosum and CA1. Seizures and altered intrahippocampal EEG activity were observed in chronically demyelinated mice. CA1 pathology included astrogliosis and alterations to aquaporin-4 expression. Pyramidal layer atrophy and parvalbumin + interneuron loss occurred in the CA1 of chronically demyelinated mice. Abstract: Multiple sclerosis (MS) patients are three to six times more likely to develop epilepsy compared to the rest of the population. Seizures are more common in patients with early onset or progressive forms of the disease and prognosticate rapid progression to disability and death. Gray matter atrophy, hippocampal lesions, interneuron loss, and elevated juxtacortical lesion burden have been identified in MS patients with seizures; however, translational studies aimed at elucidating the pathophysiological processes underlying MS epileptogenesis are limited. Here, we report that cuprizone-mediated chronically demyelinated (9–12 weeks) mice exhibit marked changes to dorsal hippocampal electroencephalography (EEG) and evidence of overt seizure activity. Immunohistochemical (IHC) analyses within the hippocampal CA1 region revealed extensive demyelination, loss of parvalbumin (PV + ) interneurons, widespread gliosis, and changes in aquaporin-4 (AQP4) expression. Our results suggest that chronically demyelinated mice are a valuable model with which we may begin to understand the mechanisms underlying demyelination-induced seizures.